Genetic insights into the complexity of premature ovarian insufficiency - Linhang Nie; Xiaojie Wang; Songyuan Wang; Zhidan Hong; Mei Wang (BMC, 2024)
Abstract Premature Ovarian Insufficiency (POI) is a highly heterogeneous condition characterized by ovarian dysfunction in women occurring before the age of 40, representing a significant cause of female infertility. It manifests through primary or secondary amenorrhea. While more than half of POI cases are idiopathic, genetic factors play a pivotal role in all instances with known causes, contributing to approximately 20-25% of cases. This article comprehensively reviews the genetic factors associated with POI, delineating the primary candidate genes. The discussion delves into the intricate relationship between these genes and ovarian development, elucidating the functional consequences of diverse mutations to underscore the fundamental impact of genetic effects on POI. The identified genetic factors, encompassing gene mutations and chromosomal abnormalities, are systematically classified based on whether the resulting POI is syndromic or non-syndromic. Furthermore, this paper explores the genetic interplay between mitochondrial genes, such as Required for Meiotic Nuclear Division 1 homolog Gene (RMND1), Mitochondrial Ribosomal Protein S22 Gene (MRPS22), Leucine-rich Pentapeptide Repeat Gene (LRPPRC), and non-coding RNAs, including both microRNAs and Long non-coding RNAs, with POI. The insights provided serve to consolidate and enhance our understanding of the etiology of POI, contributing to establishing a theoretical foundation for diagnosing and treating POI patients, as well as for exploring the mechanisms underlying the disease.